Transformasi Digital : Meningkatkan Kualitas Pelayanan Publik Melalui Penerapan E – Government Di Kantor Kecamatan Jabung Kabupaten Malang - Hanafiah, Ali; Abidin, Alie Zainal; Zainur, Yatim (STIA MALANG, 2024)
A sub-district is an administrative regional unit in Indonesia which is under the auspices of a district or city. An sub-district head heads the sub-district and divides it into several sub-districts or villages. The implementation of regional autonomyn policies has encouraged changes in the general structure of regional government, including structural, functional and cultural changes. One of the most influential changes relates to the position, authority, duties and responsibilities of a sub-district head. Along with technological advances and referring to Presidential Instruction no. 3 of 2003, E-Government was implemented to ensure the integration of electronic document and information management and processing systems. The focus is on developing a transparent public service system. Jabung District consists of 15 villages and has a population of 78,031 people with a male population of 39,873 while a female population of 38,158 people. This research aims to find out how E-Government is implemented and public service innovations in the Jabung District Office. This research uses descriptive qualitative methods. Data collection was carried out using observation, interviews and documentation techniques. The results of this research indicate that the implementation of E-Government and public service innovation in the Jabung District Office has been running well and in accordance with applicable Standard Operating Procedures (SOP). In implementing E-Government at the Jabung District Office, there are also several things that often make people confused in managing administrative needs, such as the absence of information regarding changes to forms or policies related to direct electronic based government administration or clear information via print or electronic media. so it can be said that it is still not optimal.